The Depiction of Liberal Feminism through the Main Character in the Novel Yellow Wife by Sadeqa Johnson - Efanda, Riska; Zamruddin, Mardliya Pratiwi (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2024)
In this research, the researcher analyzed the main female character named Pheby. There are two aims in this research, they are to identify the forms of liberal feminism through Pheby's character and to analyse the historical moments that influence the female main character in the novel. The researcher conducted this research using the theory of liberal feminism by Rosemarie Tong, and the Sociological Perspective by Laurenson and Swingewood. The results of this research found three aspects of liberal feminism based on Tong's theory in the form of equal education, equal liberty, and equal rights. The historical moments that occur in the novel are reflected in liberal feminism as portrayed by the main female character.